Level-2 node clustering coefficient-based link prediction - Kumar A.; Singh S.S.; Singh K.; Biswas B. (My University, 2025)
Link prediction finds missing links in static networks or future (or new) links in dynamic networks. Its study is crucial to the analysis of the evolution of networks. In the last decade, lots of works have been presented on link prediction in social networks. Link prediction has been playing a pivotal role in course of analyzing complex networks including social networks, biological networks, etc. In this work, we propose a new approach to link prediction based on level-2 node clustering coefficient. This approach defines the notion of level-2 common node and its corresponding clustering coefficient that extracts clustering information of level-2 common neighbors of the seed node pair and computes the similarity score based on this information. We performed the simulation of the existing methods (i.e. three classical methods viz., common neighbors, resource allocation, preferential attachment, clustering coefficient-based methods (CCLP and NLC), local naive based common neighbor (LNBCN), Cannistrai-Alanis-Ravai (CAR), recent Node2vec method) and the proposed method over 11 real-world network datasets. Accuracy is estimated in terms of four well-known single point summary statistics viz., area under the ROC curve (AUROC), area under the precision-recall curve (AUPR), average precision and recall. The comprehensive experiment on four metric and 11 datasets show the better performance results of the proposed method. The time complexity of the proposed method is also given and is of the order of time required by the existing method CCLP. The statistical test (The Friedman Test) justifies that the proposed method is significantly different from the existing methods in the paper. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.